(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
Now-a-days, researchers focus on the use of smart materials due to their multiple functional capabilities. A “smart material” is one having a nano level structure that can responds in a specialised and controlled way to influence on its sensing mechanisms. Due to the multiple properties of smart materials, they have a great influence on current analytical methods and diagnostic strategies by reorganizing the sensing modules for nano-sized objects (protein biomarkers and viruses) and biomolecules detection. Incontestably, current sensing mechanisms need a continuous update for addressing the growing challenges in the field of diagnosis for viruses because these viruses altered and spread rapidly from person-topersons. It becomes critical to take into consideration several factors for viral diagnosis ranging from the type and quality of specimen collected, mode of transport, time of specimen collection, level of accuracy or specificity, viral detection sensitivity, and the type of diagnostic method used. In this review, we briefly explained the principle and different types of smart materials being used for diagnosing infectious viruses. The development in the field of smart material based nano sensors with resource-scarce settings is further discussed and elaborated the pros and cons of current methods for viral detection as a conclusion and future perspective.